2016
DOI: 10.19056/ijmdsjssmes/2016/v5i1/83537
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Profile and Response to First-Line Anti-Retroviral Therapy in Human Immunodeficiency Virus Infected Patients in Manipur

Abstract: <strong>Background:</strong>Knowledge of demographic profiles and baseline characteristics of HIV infected patients is essential for devising prevention strategies. Analysis of factors influencing improvement in CD4 cell count will help to determine prognosis and better implementation of ART.<p><strong>Objectives:</strong> This retrospective study was conducted on HIV patients in Manipur, to assess clinical profile and factors influencing baseline immunological status and response… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 22 publications
(23 reference statements)
0
3
0
Order By: Relevance
“…HIV promotes hepatic fibrogenesis by production of reactive oxygen by hepatocytes through a Kappa-dependent pathway, this effect is enhanced in the presence of HCV. [ 25 ] Recent studies from Manipur, India,[ 6 ] Asia,[ 26 ] Switzerland,[ 27 ] and Australia[ 28 ] have postulated that patients coinfected with HIV/HBV/HCV appear to have a poorer response to HAART in terms of CD4+ T-cell count changes. A Chinese study also inferred similar results in HIV/HBV coinfected individuals at 48 months post-ART both in terms of CD4+ T-cell count and HIV-1 RNA suppression.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…HIV promotes hepatic fibrogenesis by production of reactive oxygen by hepatocytes through a Kappa-dependent pathway, this effect is enhanced in the presence of HCV. [ 25 ] Recent studies from Manipur, India,[ 6 ] Asia,[ 26 ] Switzerland,[ 27 ] and Australia[ 28 ] have postulated that patients coinfected with HIV/HBV/HCV appear to have a poorer response to HAART in terms of CD4+ T-cell count changes. A Chinese study also inferred similar results in HIV/HBV coinfected individuals at 48 months post-ART both in terms of CD4+ T-cell count and HIV-1 RNA suppression.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies from India and around the world have reported that HBV/HCV coinfection did not affect CD4+ T-cell counts and HIV-1 viral load suppression after ART. [ 5 6 7 9 ] It has been hypothesized that splenic sequestration of lymphocytes due to HBV-related hepatic fibrosis may be responsible for lower CD4+ T-cell recovery. [ 30 ] Many underlying comorbid conditions, other OIs, small sample size, and lack of compliance/adherence may affect these results.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation